The Fourth/Final-Year University Student Future Professional Career: Analysis of Factors and Personal Qualities - V. Lamanauskas; D. Augiene (University of Sofia, 2017)
Career management as a lifelong lasting process becomes very actual in today's modern society because of many reasons. The environment becomes turbulent, in a general sense; therefore, it is natural that career environment, basically, is chaotic as well. Nevertheless, career for many people is, undoubtedly, very important, because it is directly related to life quality. Professional activity satisfies almost all human needs: physiological, safety, social, attainment, self-realisation, independence, autonomy and other. The efficiency of the mentioned activity and the ability of the personality to construct his career are closely related things. Individual's career process studies are especially popular recently, because deeper career perception helps to understand the most important relations between man and work, career management and constant learning, helps not only to know man's abilities, but also the abilities to give oneself to modern environment, to understand career projection possibilities, to plan one's professional future. Seeking to analyse final-year university student position regarding career questions, a written form survey was carried out. The research was carried out between September 2015 and March 2016. The research sample (185) was structured applying a consecutive 'bunch' system. The respondents from three Lithuanian universities Klaipėda, Vilnius and Šiauliai, were selected in the sample. Professional career parameters were evaluated: career conception, the importance of work values and abilities, study influence, promoting and limiting factors and personal qualities. The research is grounded on a mixed strategy, when quantitative and qualitative research approach is combined. The obtained results, based on qualitative analysis, about professional personal career promoting and limiting factors and personal qualities are presented in this research.